10b-2=4b-14

Simple and best practice solution for 10b-2=4b-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10b-2=4b-14 equation:


Simplifying
10b + -2 = 4b + -14

Reorder the terms:
-2 + 10b = 4b + -14

Reorder the terms:
-2 + 10b = -14 + 4b

Solving
-2 + 10b = -14 + 4b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-4b' to each side of the equation.
-2 + 10b + -4b = -14 + 4b + -4b

Combine like terms: 10b + -4b = 6b
-2 + 6b = -14 + 4b + -4b

Combine like terms: 4b + -4b = 0
-2 + 6b = -14 + 0
-2 + 6b = -14

Add '2' to each side of the equation.
-2 + 2 + 6b = -14 + 2

Combine like terms: -2 + 2 = 0
0 + 6b = -14 + 2
6b = -14 + 2

Combine like terms: -14 + 2 = -12
6b = -12

Divide each side by '6'.
b = -2

Simplifying
b = -2

See similar equations:

| -(5x-10)=5 | | -5+2x-7x=35 | | a=160m+215 | | 4x-22=2x+12 | | -4m+2+1m=23 | | 2p-3=7 | | 15m+4-9m= | | -3x-7x=97 | | 6x+6=-x+55 | | 0.5=0.4y-0.25y | | 2x+6=4x+12 | | 3(-3x-2)-4x-5=-3 | | 5x-2x=168 | | .4(x-12)=1.2(x-4) | | 2(3a-4.2)=5a | | 6g-9/3=g | | 4(m+1)-2(3m+1)=-3(m-7)+5 | | z-2/3=1/8 | | 3(s+1)-5=3s-2 | | 5x-27=-4x | | -4-5x=7-x | | 5x+9+8=4 | | 2.85s-7=12.85s-2 | | ax+by=c(y) | | 2(x+5)+3= | | 2.5(x-2)-6=9 | | -2x-9=3x+4 | | b-31=-63 | | 4(2s-1)=-8(.5-s) | | 17+n=21 | | 9x-10x+4=-2 | | N(12)= |

Equations solver categories